A Distinct Endocytic Mechanism of Functionalized-Silica Nanoparticles in Breast Cancer Stem Cells. Issue 1 (December 2017) - Sun, Jiadong; Liu, Yajing; Ge, Min; Zhou, Guoqiang; Sun, Wentong; Liu, Dandan; Liang, Xing-Jie; Zhang, Jinchao
Abstract Nanoparticles provide new fields for life medical science application, including targeted-drug delivery and cancer treatment. To maximize the delivery efficiency of nanoparticle, one must understand the uptake mechanism of nanoparticle in cells, which may determine their ultimate fate and localization in cells. Recently, the proposed-cancer stem cell (CSC) theory has been attracted great attention and regarded as new targets for the new nanodrug developmet and cancer therapies. The interaction between nanoparticles and cancer cells has been extensively studied, but the uptake mechanism of nanoparticles in CSCs has received little attention. Here, we use the pharmacological inhibitors of major endocytic pathways to study the silica nanoparticle (SiNP) uptake mechanisms in the human breast adenocarcinoma cell line (MCF-7) and MCF-7-derived breast cancer stem cells (BCSCs). The results demonstrate that the uptake of SiNPs, particularly amino-functionalized SiNPs, in MCF-7 cells is strongly affected by the actin depolymerization, whereas BCSCs more strongly inhibit the amino-functionalized SiNP uptake after the scavenger receptor disruption. These findings indicate a distinct endocytic mechanism of functionalized SiNPs in BCSCs, which is significant for designing ideal nanosized drug delivery systems and improving the selectivity for CSC-targeted therapy.